Trade Reforms, Farm Productivity, and Poverty in Bangladesh - Klytchnikova, Irina (World Bank, Washington, DC, 2012)
This paper analyzes the distributional impacts of trade reforms in rural areas of Bangladesh. The liberalization of trade in irrigation equipment and fertilizer markets during the early 1990s has led to structural changes in the agricultural sector and a significant increase in rice productivity. A resulting increase in output has been associated with a decline in producer and consumer rice prices of approximately 25 percent. Using a combination of ex-post and ex-ante approaches, the authors investigate the implications of the changes in rice productivity and prices for the welfare of households. They find that the net effects of increased rice productivity and lower rice prices have benefited the poor. Regardless of the particular category analyzed, the poorest households emerged as being particularly positively affected by reforms in the 1990s. This mainly reflects the fact that they are predominantly net rice buyers in both urban and rural markets. In contrast, large net sellers of rice, among the better-off households in the rural areas, were the main losers. Since net buyers in rural areas tend to be poorer than net sellers, trade liberalization has benefited the poor. Although the authors are not able to test empirically what has happened to the welfare level of agricultural wage earners, secondary evidence suggests that they have gained from trade liberalization.